2018
DOI: 10.1016/j.stem.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Activation Screens Systematically Identify Factors that Drive Neuronal Fate and Reprogramming

Abstract: SUMMARY Comprehensive identification of factors that can specify neuronal fate could provide valuable insights into lineage specification and reprogramming, but systematic interrogation of transcription factors, and their interactions with each other, has proven technically challenging. We developed a CRISPR activation (CRISPRa) approach to systematically identify regulators of neuronal fate specification. We activated expression of all endogenous transcription factors and other regulators via a pooled CRISPRa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(142 citation statements)
references
References 50 publications
3
139
0
Order By: Relevance
“…In addition to the Ngn2-driven generation of glutamatergic neurons (Fernandopulle et al, 2018;Wang et al, 2017;Zhang et al, 2013) used here, induced expression of different transcription factors yield other types of neurons, such as motor neurons (Hester et al, 2011;Shi et al, 2018) and inhibitory neurons (Yang et al, 2017). Systematic screens are beginning to uncover additional combinations of transcription factors driving specific neuronal fates (Liu et al, 2018;Tsunemoto et al, 2018). Thus, iPSC technology could be used to generate different neuron types from an isogenic parental cell line, which would facilitate parallel CRISPR screens to dissect neuronal subtype specific gene function.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the Ngn2-driven generation of glutamatergic neurons (Fernandopulle et al, 2018;Wang et al, 2017;Zhang et al, 2013) used here, induced expression of different transcription factors yield other types of neurons, such as motor neurons (Hester et al, 2011;Shi et al, 2018) and inhibitory neurons (Yang et al, 2017). Systematic screens are beginning to uncover additional combinations of transcription factors driving specific neuronal fates (Liu et al, 2018;Tsunemoto et al, 2018). Thus, iPSC technology could be used to generate different neuron types from an isogenic parental cell line, which would facilitate parallel CRISPR screens to dissect neuronal subtype specific gene function.…”
Section: Discussionmentioning
confidence: 94%
“…CRISPRa is a powerful approach to elucidate the cellular and genetic basis of various biological phenomena in bacteria and higher organisms (Konermann et al, 2015;Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While further (meta-)analysis will likely shed more light on these different views, it is not surprising that the most efficient and reliable conversion strategies involve the combined expression of Ascl1 and Ngn2 [9,10,31,35]. Recently, it has been suggested that a huge variety of TF combinations can be applied to generate subtype-specific iNs from fibroblasts (Table 1), and TF screening studies for iN conversion have led to the identification of additional pro-neuronal factors, such as Brn3a/b/c, Brn4s, and Ezh2 [36,37]. Interestingly, differences in TF choice were noted between species, as, for example, Neu-roD1 and Ngn2 were used predominantly in human iN protocols and not in rodent protocols, but no mouse-specific or human-specific TF combinations have been established thus far [6,25].…”
Section: Enabling In Conversionmentioning
confidence: 99%
“…Further, unlike for most other human cell types, primary human neuronal cultures of defined brain regions are not available for direct comparison, which further complicates the definition of gold standard criteria. By any means, the value of cell models should be measured by how well they perform their respective tasks, and these tasks might range from teaching us more about a complex disease, or how well they integrate into a neuronal circuit following transplantation [6,[33][34][35][36][37][38]114,115].…”
Section: Updating Our Criteria To Define Neuronsmentioning
confidence: 99%